(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Â Â Â Â Â Â Simulation study of Adrenaline synthesis from Phenylalanine has been carried out using semi-empirical methods (PM3) and density functional theory (DFT) STO-3G level of theory . Geometrical properties and vibration mods have been calculated for all structures. Different probable products have been suggested for each reaction and the most probable products being selected depending upon the electronic properties to prove the pathway of reactions thatâ€™s needed to synthesis adrenaline in the human body. Â Â Â Â Â Â Â Â Â The calculations show the most probable product than other structurs due its energetic values of total energy, energy barrier value, heat of formation, zero point energy, imaginary frequency and rate constant thatâ€™s equal to (5.554*1012, 5.572*1012, 7.857*1012, 1.331*1013,1.116*1013) respectively by s-1 units. Thermodynamic functions (âˆ†H, âˆ†S, âˆ†G) have been calculated for five steps reactions of Adrenaline synthesis . In reaction 1 equal to (-69.468, 1.37*10-4, -66.610), reaction 2 (-46.453, 3.044*10-3, -64.710), reaction 3 (-63.734, 0.022, 138.900), reaction 4 (87.036, 8.631*10-3, -451.510) and reaction 5 (-6.722,-0.025, 346,800) respectively by kCal/mol, kCal/mol/deg, and kCal/mol respective units. The chemical reactivity or energy gap has been calculated for the most probable products in the pathway of adrenaline synthesis .